Life stress as a risk factor for sustained anxiety and cortisol dysregulation during the first year of survivorship in ovarian cancer. Issue 16 (15th June 2018) - Armer, Jessica S.; Clevenger, Lauren; Davis, Lauren Z.; Cuneo, Michaela; Thaker, Premal H.; Goodheart, Michael J.; Bender, David P.; Dahmoush, Laila; Sood, Anil K.; Cole, Steven W.; Slavich, George M.; Lutgendorf, Susan K.
Abstract : BACKGROUND: Patients with ovarian cancer often report elevated anxiety at diagnosis that decreases posttreatment. However, a minority of patients experience sustained anxiety. Few studies have examined risk factors for persistent anxiety or its physiologic sequelae in ovarian cancer. Therefore, the authors investigated associations between prior life events, anxiety, inflammation (plasma levels of interleukin‐6), and diurnal cortisol profiles in patients with ovarian cancer during the first year postdiagnosis. METHODS: Participants (n = 337) completed surveys and had blood and salivary sampling prediagnosis, postchemotherapy (6 months), and 12 months after diagnosis. The Life Events and Difficulties Schedule was administered to a patient subset (n = 127) within 1 month of diagnosis. Linear mixed‐effects models were used to analyze relations between anxiety and biologic variables over time. Linear regression models assessed whether anxiety trajectories mediated associations between prior stress exposure and biologic variables. Age, chemotherapy at 1 year, and cancer stage were covariates. RESULTS: Decreased anxiety was associated with a more normalized cortisol slope over time (β = 0.092; P = .047). Early life adversity was related to flatter cortisol slopes over time (β = −0.763; P = .002); this relation was partially mediated by anxiety trajectory ( P = .046). More danger‐related events prediagnosis were associated with sustained anxiety (β = 0.537; P = .019) and flatter cortisol slopes over time (β = −0.243; P = .047); anxiety partially mediated the relation between danger and cortisol slope ( P = .037). Neither anxiety nor prior stress exposure was related to levels of interleukin‐6. CONCLUSIONS: Because dysregulated cortisol has been related to fatigue, poorer quality of life, and shorter survival in patients with ovarian cancer, those who have prior life events and chronic anxiety during the first year postdiagnosis may be at risk for more negative outcomes. Cancer 2018 . © 2018 American Cancer Society . Abstract : Associations between prior life stressors, anxiety, inflammation, and diurnal cortisol profiles are investigated in patients with ovarian cancer. The results indicate that early life stress and adulthood stressors involving danger contribute to persistent anxiety and dysregulated cortisol patterns during the first year after ovarian cancer diagnosis.